Distribution of mutations in DNMT3A gene and the suitability of mutations in R882 codon for MRD monitoring in patients with AML - Jeziskova, Ivana; Musilova, Milena; Culen, Martin; Foltankova, Veronika; Dvorakova, Dana; Mayer, Jiri; Racil, Zdenek (International journal of hematology, 2015)
The DNA methyl-transferase 3A gene (DNMT3A) is the third most frequently mutated gene in cytogenetically normal acute myeloid leukemia (CN-AML) patients (20-30 %), who belong to a group of patients with intermediate risk. About 60 % of mutations in this gene have been identified in the arginine codon R882. To date, there is no consensus on whether these mutations can be used as biomarkers for monitoring of minimal residual disease and management of preemptive AML therapy. We studied the occurrence of mutations in the DNMT3A gene in our cohort of patients and their persistence during AML treatment. Using next-generation sequencing, we identified four mutations in 11/25 of our analyzed patients--frequent R882C and R882H mutations, rare Y735S mutation, and a novel L347P mutation. Mutation R882C was detected in 5/11, R882H in 4/11 patients, and Y735S and L347P in one patient each. In 4/7 patients initially carrying mutations in the R882 codon, we found the persistence of mutations also during complete remission with, however, no correlation to AML kinetics. Our findings suggest that mutations in the DNMT3A gene can only be used as a biomarker for those AML patients in whom DNMT3A mutation is lost after therapy.
Keywords: senioři; Neoplasm Proteins; reziduální nádor; nádorové proteiny; Next-generation sequencing; Amino Acid Substitution; missense mutace; substituce aminokyselin; Middle Aged; Neoplasm, Residual; mužské pohlaví; DNA Methyltransferase 3A; Codon; DNA methyltransferasa 3A; Adult; Leukemia, Myeloid, Acute; Mutation, Missense; Monitoring, Physiologic; Biomarkers, Tumor; ženské pohlaví; nádorové biomarkery; DNA-(cytosin-5-)methyltransferasa; Humans; AML preleukemic stem cells; DNA (Cytosine-5-)-Methyltransferases; kodon; lidé středního věku; akutní myeloidní leukemie; DNMT3A gene mutations; dospělí; monitorování fyziologických funkcí; Female; Aged; MRD; lidé; Male